Relationship between the saccus endolymphaticus and the fourth ventricle of the brain of the domestic fowl (Gallus gallus f. domestica) - Klika, E; Zajícová, A (Folia morphologica, 1989)
The fine structure of the wall of the SE was determined exactly and its relationship to the cisternae (the evaginations of the roof of the fourth ventricle extending to the SE) was defined. The way in which the cisterna is formed was defined and the development of its fine structure was described by comparing serial sections from 19-day embryos and adult fowls. Like the SE, the cisternae are lodged in the angle between the cerebellum and the medulla oblongata, in the subarachnoid space. The terminal segment of the cisterna lies in the immediate vicinity of the mesenchymal epithelium bordering the basal labyrinth of the SE cells. Collagen trabeculae keep the SE and the cisternae suspended in the subarachnoid space. The cisternae and trabeculae are wrapped in mesenchymal epithelium. The cisterna is avascular and does not communicate with the SE. The cisterna is lined internally with simple squamous epithelium (modified neural epithelium of the roof of the fourth ventricle). The bodies of the cells bulge into the lumen of the cisterna in the region of localization of their nucleus. The epithelium is seated on a pronounced basal lamina. The surface turned towards the subarachnoid space is lined continuously with mesenchymal epithelium without a basal lamina. The cells of the cisternal epithelium are connected by tight junctions of the type of zonulae occludentes and desmosomes. The basal lamina is continuous and distinct. The mesenchymal epithelium of the subarachnoid space has no basal lamina, as on the subarachnoid surface of the SE, the cisternae, the trabeculae, the pia mater and the arachnoidea.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Endolymphatic Sac; drůbež; Poultry; Animals; mozkové komory; vnitřní ucho; Ear, Inner; Cerebral Ventricles; saccus endolymphaticus; zvířata